A dynamical (time-harmonic) axisymmetric stress field in a finitely prestretched multilayered slab on a rigid foundation - Zamanov, A. D.; Suleimanov, T. R.; Akbarov, S. D. (SPRINGER, 2006)
Within the framework of a piecewise homogeneous body model, with the use of the three-dimensional linearized theory of elastic waves in initially stressed bodies, the dynamical (time-harmonic) axisymmetric stress field in a finitely prestretched multilayered slab resting on a rigid foundation is studied. It is assumed that the slab consists of,two-layer packets. The elasticity of layer materials is described by the Treloar potential. It is assumed that the material of the lower layer in the packets is more rigid than that of the upper one. Numerical results are presented for the cases where the number of layers (packets) in the slab is 2 (1), 4 (2), or 6 (3). These results concern the normal stresses acting on the interface between the layers of the first, upper packet and on the interface between the first and second packets. The influence of the number, prestretch level, and thickness of the layers on relationships between the stresses and the frequency of the external force is analyzed.
Keywords: forced vibration; multilayered slab; finite prestretching; stress distribution; incompressible material; HALF-SPACE; PROPAGATION; VIBRATION; SURFACE; Mechanics; Materials Science; Polymer Science